Research on non-orthogonal transmission strategy for content delivery in caching networks - Long YANG; Hanyang LI; Mengmeng REN; Bingtao HE; Yuchen ZHOU; Jian CHEN (Tongxin xuebao)
A two-stage adaptive non-orthogonal/orthogonal multiple access transmission scheme was designed for content delivery scenarios in wireless caching networks.For the scheme, a high-reliability user scheduling strategy was proposed, and the analytical expression of the outage probability and its asymptotic expression in high signal-to-noise ratio regime were derived by theoretical analysis.The analysis results indicate that the proposed strategy can achieve full spatial diversity gain.Simulation results demonstrate that compared with the instantaneous channel state information-based scheduling strategy, the random scheduling strategy, and the conventional orthogonal multiple access transmission strategy, the proposed strategy can achieve better content delivery reliability than existing strategies by obtaining the spatial diversity gain.